Risk estimation of the disaster waste generated by both ground motion and tsunami due to the anticipated Nankai Trough earthquake. (26th February 2021) - Ishibashi, Hiroki; Akiyama, Mitsuyoshi; Kojima, Takayuki; Aoki, Koki; Koshimura, Shunichi; Frangopol, Dan M.
Abstract: The amount of disaster waste is one of the most important performance indicators in quantifying the resilience of a community. In fact, disaster waste can have significant negative impacts on the environment in affected regions and hinder the postdisaster recovery process. Appropriate disaster waste management should be developed in Japan before the occurrence of the Nankai Trough earthquake. It is expected that the seismic and tsunami intensities caused by the anticipated Nankai Trough earthquake will be substantially larger than those caused by the 2011 Great East Japan earthquake. In this paper, a risk‐based methodology is presented for estimating the amount of disaster waste generated by both the ground motions and the tsunami due to the anticipated Nankai Trough earthquake. First, Monte Carlo simulation‐based probabilistic hazard analyses are performed to obtain seismic and tsunami hazard curves considering the uncertainty associated with fault movement along the Nankai Trough. Structural damage data associated with past earthquakes are used to develop seismic and tsunami fragility curves. The amount of disaster waste generated from a single structure is defined as the generation unit and is determined based on past disasters. Finally, with the aid of a geographic information system, the risk of disaster waste can be estimated using the hazard and fragility curves and the generation units. As an illustrative example, the risk curves and expected values associated with disaster waste in Mie Prefecture, Japan, are estimated based on the proposed framework.